Improved Post-quantum Hash Based One-Time Key Mechanism - Gorbenko, Yu.I.; Isirova, K.V. (Radiotekhnika, 2017)
The necessity of developing new electronic signature mechanisms, which will be relevant and can be applied in the post-quantum period, is grounded. The main properties of existing mechanisms, their advantages and disadvantages are given. An improved POTS mechanism is proposed. The essence is described, research of properties by criteria of complexity - cryptographic stability is presented, advantages and disadvantages and conditions and possibilities of its use in various applications of the post-quantum period are determined.